Characterisation of stress and moisture-dependent resilient behaviour for compacted clays in South China. Issue 1 (2nd January 2020) - Zhang, Junhui; Peng, Junhui; Zheng, Jianlong; Yao, Yongsheng
Abstract : In order to predict the resilient modulus of compacted clays, the material indicator tests, repeated load triaxial test, and pressure plate test for compacted clays from South China were carried out. The soil–water characteristic curve (SWCC) was described using the Fredlund and Xing's model. And a logarithmic function between the soil suction and resilient modulus was built. Then, a new variable named the minimum bulk stress was defined to separate the shear effect of soil samples from the bulk stress, which avoids the bulk stress reflects two contrary effects, namely hardening effect and softening effect. Subsequently, the influences of the degree of compaction, soil suction, minimum bulk stress, and octahedral shear stress on the resilient modulus were analysed. In the following, a new resilient modulus prediction model of compacted clays, which took the soil suction, minimum bulk stress, and octahedral shear stress as the model variables, was developed and verified using the data of different cohesive soils from this study and existing literatures. The results show that the new model matched these data well and have a high prediction accuracy, which indicates that this new model is reasonable and widely applicable.